2000
DOI: 10.1111/j.1346-8138.2000.tb02176.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Giant Pencil‐Core Granuloma

Abstract: Although pencil injury is a common occurrence, only six cases of so-called pencil-core granuloma have been reported. All of these granulomas were relatively small, and most of them simulated malignant melanoma. We report a giant pencil-core granuloma that developed on a patient's right palm. Its gross appearance was quite different from that of other cases previously reported; it was much larger and resembled a hemangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…However, some examinations reported that many giant cells and epithelioid cells were observed in pencil core granuloma [2, 3]. Hatano et al attributed this difference to granulomatous reactions at different stages [4].…”
mentioning
confidence: 99%
“…However, some examinations reported that many giant cells and epithelioid cells were observed in pencil core granuloma [2, 3]. Hatano et al attributed this difference to granulomatous reactions at different stages [4].…”
mentioning
confidence: 99%
“…These have been more commonly reported in the orbit and the chest. There is a potential for long term complications like lead arthropathy (Peh and Reinus, 1995), granuloma (Yoshitatsu and Takagi, 2000) and soft-tissue sarcoma (Kulkarni et al, 2003). Osteomyelitis of the femoral neck following stab wounds by pencil has been previously reported (Volpin et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Graphite foreign body granuloma(pencil core granuloma) is characterized by a delayed foreign body reaction against the remaining fragments of pencil lead and at the macroscopic level, it resembles malignant melanoma 2,12 . The occurrence of pencil core granulomas is rare, only a few case reports have been documented in literature [1][2][3]5,6,10,12 . Pencil core granulomas as well as silica granulomas appear to have delayed reactions, with lag periods of 1.5-58 years between injury and granuloma formation 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Injury by a pencil is common and usually trivial [1][2][3] . However, several reports indicate that stab injuries caused by pencils can result in undesirable reactions, such as pigmentation, abscess formation, and soft tissue reaction [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation